Materia civil N° 01918-2014-0-1903-JR-CI-01. Demandante: Sergio Fernando Chuquipiondo Guardia y otros. Demandado: Eva Judith Chuquipiondo Guardia. Materia: nulidad de acto jurídico. Órgano jurisdiccional: Primer Juzgado Civil de Maynas/Materia constitucional N° 01105-2012-0-1903-JR-CI-02. Demandante: Lina Victoria Ramírez Lavi. Demandado: Dirección Regional de Salud de Loreto. Materia: aación de cumplimiento. Órgano jurisdiccional: Segundo Juzgado Civil de Maynas - Vargas Guevara, Xiomara Alexandra Yahayra (2022)
In the First Civil Court of Maynas, the plaintiffs Sergio Chuquipiondo Guardia, Carlos Chuquipiondo Guardia and Roger Chuquipiondo Guardia, filed a lawsuit of Nullity of Legal Act against Eva Chuquipiondo Guardia, they filed a cumulative lawsuit of Nullity of Legal Act, having as main claim to declare the nullity of the purchase-sale celebrated between the defendant (as buyer) and the one who in life was her father Eugenio Chuquipiondo Vásquez (as seller). The Judge of First Instance declared the claim UNFOUNDED, considering that the real estate corresponded to Mr. Eugenio Chuquipiondo Vásquez as the sole owner, therefore, it was his own property. In this sense, there is no legal limitation for an owner to freely dispose of his property for valuable consideration. The collegiate of the Civil Court of Loreto, revokes the first instance sentence that declared the claim unfounded; reforming it, declares the claim FOUNDED, considering that the ownership of the property subject of sub litis corresponds to the marital partnership because it was acquired after the marriage. The defendant filed an appeal for cassation. The Transitory Civil Chamber of the Supreme Court of Justice of the Republic resolved declaring the appeal of Cassation IMPROCEDENT.